Serine and Alanine as Corrosion Inhibitors for 5083 AA in Aqueous Solutions - Zainab W. Ahmed (Journal of Global Pharma Technology, 2016)
By means of potentiodynamic polarization methods, inhibiting the influence of serine and alanine on 5083 AA corrosion in 0.1 mol.dm-3 sodium hydroxide and 140.6 mol. dm-3 NaCl">  over temperature range (298-313) K was investigated. Potentiodynamic polarization results specified that these amino acids functioned as a functional inhibitor in an alkaline environment. The inhibiting efficiency raises as the inhibitor concentration raises. However, it drops as temperature rises. The maximum efficiency value found with alanine was 73 under 298 k and 1410-2 mol. dm-3">  alanine concentration. The adsorption of the amino acids complies with Langmuir adsorption isotherm. Some thermodynamic parameter 14âˆ†Gads">  and activation energy 14Ea">  have been computed to demonstrate the process of corrosion inhibition. The kinetic limitations have been evaluated by means of Arrhenius theorem. An appropriate mechanism has projected for 5083 AA corrosion in alkaline medium. The surface morphology of uninhibited and inhibited samples was investigated using an optical microscope.Keyword: Corrosion inhibition, 5083AA, Amino acids, Free energy of adsorption, Adsorption mechanism.